Enhancing Scientific Argumentation Skills in High School Physics: A Blended Learning Approach with Project-based Instruction - Putri, Indah Ardita; Suana, Wayan; Suyanto, Eko; Hasan, Muhammad Fikri (STKIP Singkawang, 2024)
This empirical investigation delves into the application of blended learning within project-based instruction (project-based blended learning), within the framework of physics education for eleventh-grade students in a high school setting. The primary aim is to unravel the repercussions of this teaching model on the students' proficiency in scientific argumentation, particularly in the domain of optical instruments. Employing the non-equivalent control group design, the study enlists two classes: the experimental and the control group at a senior high school in Bandar Lampung, Indonesia, encompassing a total of 60 students during the academic year 2022/2023. Quantitative evaluation of scientific argumentation skills was conducted through tests, while qualitative insights into student reactions were garnered via an open-ended questionnaire. The findings underscore a noteworthy enhancement in the scientific argumentation abilities of the experimental group (n-gain: 0.69) as opposed to the control group (n-gain: 0.40), with the test of mean differences yielding a significance level (2-tailed) of 0.00. Qualitative scrutiny of the data also brought to light a more pronounced positive reception from students in the experimental cohort, lending support to the potential refinement of the project-based blended learning model for the augmentation of students' scientific argumentation aptitude.